SDN Resource Management Mechanism Based on Bilateral Market's Multi-Homed Architecture - Bin Zhuge; Li Deng; Guowei Dai; Weiming Wang; Julong Lan (Dianxin kexue)
In recent decades, the existing IP network has little innovation, SDN may be the next round of the network technology revolution, and it will bring the huge market potential. From the SDN archiecture by analyzing the OpenDaylight project and the concept of bilateral market, a SDN resource management architecture based on bilateral market and a multi-platform selection algorithm based on the extension of FPM were proposed. In the simulation test, the advantages of the architecture were proved through task completion time and cost on single or double platform under different task allocation strategy, and the reasonable allocation of resources was implemented and the reliability in SDN was improved.